Предмет: Математика, автор: supercatcatcatcat66

Упростите выражения -2(2,7x-1)-(6-3,4x)+8(0,4x-2) и вычислите его значение при x= -5/6​

Ответы

Автор ответа: jekadva
3

Ответ:

-21

Пошаговое объяснение:

-2(2,7x-1)-(6-3,4x)+8(0,4x-2) = -5,4x + 2 - 6 + 3,4x + 3,2x - 16 = 1,2x - 20

при x = -5/6

1,2x - 20 = 1,2*(-5/6) - 20 = -1 - 20 = -21

Автор ответа: Reiana
2

Ответ:

-2(2,7х-1)-(6-3,4х)+8(0,4х-2)=

=-5,4х+2-6+3,4х+3,2х-16=

Ищем подобные:

-5,4х и 3,4х и 3,2х

2 и -6 и -16

=1,2х-20

При х=-5/6

=1,2 * (-5/6)-20=1 целая 2/10 *(-5/6)-20=12/10 * (-5/6)-20=

=-2/2-20=1-20=-19

Ответ:-19


jekadva: = -2/2-20 = -1-20= -21

Ответ:-21
Похожие вопросы